Effect of BARI Wheat Varieties on Seed Germination, Growth and Yield under Patuakhali District - Al-Musa, MAA; Ullah, MA; Moniruzzaman, M; Islam, MS; Mukherjee, A (Journal of Environmental Science and Natural Resources, 2013)
A pot experiment was carried at Patuakhali Science and Technology University to study the performance of some BARI wheat varieties under the coastal area of Patuakhali. Four wheat varieties viz. BARI ghom-23, BARI ghom-24, BARI ghom-25 and BARI ghom-26 were planted in the field to evaluate their comparative performance in respect of germination percentage, growth, yield and yield attributing characters. Among the four varieties, BARI ghom-26 showed superior performance irrespective of all parameters studied except total dry matter content (TDM) and yield reduction percentage. Among the BARI varieties, BARI ghom-26 produced greater germination (61.00%) at 13 days judge against to other varieties. The taller plant (47.91 cm), higher LAI (1.84), maximum TDM (17.37 g plant-1) and effective tillers hill-1 (18.08) were also obtained with the similar variety. BARI ghom-26 was also most effective to produce the maximum grains spike-1 (38.52), higher weight of 1000-grains (49.38 g), higher grain (3.35 t ha-1) and straw (8.50 g plant-1) yield and greater HI (4.03%). So, the variety BARI ghom-26 produced the outstanding superiority among the varieties. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14816 J. Environ. Sci. & Natural Resources, 5(2): 209-212 2012